2021
DOI: 10.3389/fenrg.2021.642920
|View full text |Cite
|
Sign up to set email alerts
|

Space High-Voltage Power Module

Abstract: With the rapid development of the world’s aerospace technologies, a high-power and high-reliability space high-voltage power supply is significantly required by new generation of applications, including high-power electric propulsion, space welding, deep space exploration, and space solar power stations. However, it is quite difficult for space power supplies to directly achieve high-voltage output from the bus, because of the harshness of the space environment and the performance limitations of existing aeros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…For this purpose, high-frequency transformer-based converters are most commonly used. A literature review performed in the area of high-voltage power supplies for rapid capacitor charging showed that in most cases, topologies with full-bridge converters are used [12][13][14][15][16][17][18][19] due to the versatility of this topology and the possibility of implementing various control algorithms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, high-frequency transformer-based converters are most commonly used. A literature review performed in the area of high-voltage power supplies for rapid capacitor charging showed that in most cases, topologies with full-bridge converters are used [12][13][14][15][16][17][18][19] due to the versatility of this topology and the possibility of implementing various control algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…In [12][13][14], a simple hard-switched duty cycle control method was used, but this way of control may cause significant electromagnetic disturbance and large power losses [20]. Therefore, a method with phase-shifted modulation is much more often used [15,16]. In a large number of applications, a resonant converter can be found [17,18].…”
Section: Introductionmentioning
confidence: 99%